2021
DOI: 10.1097/ncc.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, Hope as Mediators Between Positive Coping and Resilience Among Patients With Gastric Cancer Before the First Chemotherapy

Abstract: Background Patients with gastric cancer experience severe psychological distress as a result of their cancer diagnosis and chemotherapy. Resilience is a defense mechanism that enables one to thrive amid distress. However, little research has been done to explore the formation and development mechanism of resilience among patients with gastric cancer before their first chemotherapy treatment. Objective The mediating roles of self-efficacy and hope on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…They found that blood and tumour patients with higher hope tend to have less symptom burden and suffer less pain. Hope helps patients actively cope with difficulties and increases their resilience in the face of cancer (Wu et al, 2021). Bando et al, (2018) pointed out that when hope is regarded as the core of lung cancer patient care, it is important to provide appropriate support to alleviate treatment‐related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They found that blood and tumour patients with higher hope tend to have less symptom burden and suffer less pain. Hope helps patients actively cope with difficulties and increases their resilience in the face of cancer (Wu et al, 2021). Bando et al, (2018) pointed out that when hope is regarded as the core of lung cancer patient care, it is important to provide appropriate support to alleviate treatment‐related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that higher levels of hope played an important role in reducing negative emotions, [ 56 , 57 ] because higher levels of hope led to lower anxiety levels. However, the mean DAS score was above the moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…12 It can lead to more despair, pessimism and depression, as well as lower treatment effects and longer hospital stays. 12,18,21,22 Although previous studies have explored the relationship among social support, self-efficacy, coping, and psychological resilience, it is still unknown whether these factors will affect the psychological resil-…”
Section: Introductionmentioning
confidence: 99%
“…When patients are under great pressure or trauma, they may choose this coping strategy and give up efforts to change the status quo, which can cause people to lose control of the disease and future 12 . It can lead to more despair, pessimism and depression, as well as lower treatment effects and longer hospital stays 12,18,21,22 …”
Section: Introductionmentioning
confidence: 99%